PENGELOLAAN EMOSI ANAK USIA DINI DALAM PERSPEKTIF TEORI PSIKOSOSIAL ERIK ERIKSON - Riska Meilana; Novita Rimandhani; Vava Imam Agus Faisal (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
This article aims to examine in depth the role of parents in managing emotions in early childhood based on Erik Erikson's theory of psychosocial development. The article was written using a literature study method by reviewing developmental psychology books, scientific journals, and relevant research results. The results of the study indicate that a child's success in resolving psychosocial crises in early life particularly the stages of trust, autonomy, and initiative is greatly influenced by the quality of parental care. Warm, responsive, and consistent parenting plays a vital role in helping children recognize, express, and manage emotions in a healthy manner. Thus, the role of parents is not limited to meeting a child's physical needs but also includes ongoing emotional support as a foundation for a child's psychosocial development.